Poza duopolem. Młodych Polaków wybory polityczne z 2023 roku w świetle danych zastanych i jakościowych badań własnych - Taradejna, Paweł (Studia Socjologiczno-Polityczne. Seria Nowa, 2025)
The article examines the voting attitudes of young Poles in the 2023 parliamentary elections, focusing on voters outside the PO-PiS duopoly. It draws on CBOS and ISP data, as well as original interviews with 11 young voters. The study identifies three key (young) voters’ profiles: 1) Nowa Lewica voters, motivated by progressive values (women’s rights, secularism, minority rights); 2) Trzecia Droga supporters, combining economic liberalism with concerns about democracy and public discourse; and 3) Konfederacja voters, holding anti-system and free-market views, often criticizing „social handouts”. The author notes significant gender differences and highlights that young voters’ political engagement is often conditional – they are more open to new political movements but quickly abandon them if expectations are unmet. The findings suggest a potential reconfiguration of Poland’s political landscape, with young voters acting as a transformative force. However, their low party loyalty and frustration with the establishment may also create opportunities for new, including undemocratic, political projects.